A piecewise analytical solution of Jiang's model of elastoplasticity - Lang, Holger; Dreßler, Klaus; Pinnau, René (2007)
In this article, we present an analytic solution for Jiang’s constitutive model of elastoplasticity. It is considered in its stress controlled form for proportional loading under the assumptions that the one-to-one coupling of the yield radius and the memory surface radius is switched off, that the transient hardening is neglected and that the ratchetting exponents are constant.
Keywords: Elastoplasticity; Jiang’s constitutive model; variational inequalities; rate-independency; hysteresis